The Use of Private Contracted Armed Security Personnel (PCASP) As an Anti-Piracy Measure and Solution - Afriansyah, Arie; Hartoyo, Yoga Muhammad Adhiwiratama (Padjadjaran Journal of International Law, 2023)
The sea route is one of the best options chosen by national and international traders because of lower cost when we compare it to using air freight and the increasing use of merchant ships for international trade, makes people take advantages such as sea piracy and armed robbery and a solution to protect from these things commercial vessels use the services of the Private Contracted Armed Security Personnel (PCASP) and the Private Maritime Security Company (PMSC). The absence of international regulations regarding the use of these services raises pros and cons between coastal states and with special policies in particular regarding the territorial sea of ​​a coastal state. Thus, there is a big question that the use of PCASP and PMSC is in accordance with international law with existing regulations and how Indonesia as a coastal state sees the use of such services as a solution to avoid piracy. The formation of soft laws and agreements is a way out at this time in order to maintain maritime security from the dangers of sea piracy and armed robberies.